PERAN POLITIK HUKUM DALAM PERENCANAAN PEMBANGUNAN DAERAH - Hendry John Piris (Faculty of Law, Universitas Pattimura, 2014)
Integration of the development planning area within the development system of National, all Regional Governments both Provincial and Regency/City shall prepare a planning document regional development, in the form of a Plan Long-Term Development (PLD) Regional and Medium Term Development Plan Regions with due regard to the country's financial and Planing system National development. But the fact of legislation are still many inconsistencies among others associated with the procedure, standard time, costs. To create different sets of rules and regulations, which became the legal basis for orderly behavior in order to organize the life of society, nation and state. The establishment of legislation is done through the correct process with regard orderly legislation and general principles of legislation is good. As stipulated by law number 23 of 2014,